KARAKTERISTIK BAHAN INDUK TANAH DARI FORMASI GEOLOGI KOMPLEKS ULTRAMAFIK DI SULAWESI TENGGARA - Alam, Syamsu; Sunarminto, bambang Hendro; Siradz, Syamsul Arifin (Jurnal Agroteknos, 2012)
The research aiming to study the characteristics of the soil parent material ultramafic Complex Geologic Formations in the Southeast Sulawesi has been carried out in December 2010 to  June 2011 .  Fieldwork was conducted at  two different locations, namely in  the District Lasusua, North Kolaka and in the District Puriala, Konawe. Laboratory studies were conducted using thin section rock and extraction with concentrated acid extraction using HNO3 + HF to determine the mineral composition and chemical composition of total elemental rock. The research results showed that the type of host rock found commonly included peridotite and serpentinite group which were the main constituents of the rock group  Ultarmafik complex  geological formations. The  dominant  mineral  found  in  rocks peridotite included olivine followed by some minerals such as antigorit accompaniment, enstantit, and hornblende, picotit, plagioclase feldspar and anthophyllit. The dominant mineral types found in serpentinite rocks included olivine and antigorit accompaniment followed by  minerals such as  enstantit, plagioclase feldspar and  anthophyllit. Elemental composition of the rock group ultramafic complex geological formations were characterized by low contents of SiO2  and Al2O3  compared to other rocks, as well as contained relatively high MgO, CaO and Na2O. Kata Kunci : soil parent material, geologic formations, mineral composition, ultramafic,